Leadership Style, Work Environment, and Employee Performance: The Mediating Role of Job Satisfaction - Popiandi, Deka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2025)
The research entitled The Influence of leadership style and work environment on employee performance with job satisfaction as an intervening variable at the population and civil registration service of Kerinci regency aims to investigate the direct and indirect effects of organizational factors on employee performance. Although the title refers to Kerinci Regency, the actual object of study was the employees of the Population and Civil Registration Service in Sungai Penuh City. This study employs a quantitative causality research design using questionnaires as the primary method of data collection. The sampling technique adopted is saturated sampling, with a total of 74 respondents analyzed. Data were processed using multiple linear regression analysis assisted by the SmartPLS software. The findings reveal that leadership style has a positive and significant effect on job satisfaction, and the work environment also positively and significantly influences job satisfaction. Additionally, both leadership style and work environment exert a positive and significant impact on employee performance. However, job satisfaction itself has a negative and statistically insignificant effect on employee performance. Furthermore, job satisfaction does not mediate the relationship between leadership style and employee performance, nor between the work environment and employee performance.